College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.4 - Average Rate of Change of a Function - 2.4 Exercises: 13

Answer

(a) -5 (b) -1

Work Step by Step

We are given: $h(t)=-t+\frac{3}{2}$, $t=-4$, $t=1$ (a) We calculate the net change: $h(1)-h(-4)=[-1+\displaystyle \frac{3}{2}]-[--4+\frac{3}{2}]=\frac{1}{2}-\frac{11}{2}=-5$ (b) We calculate the average rate of change: $\frac{h(1)-h(-4)}{1--4}=\frac{-5}{5}=-1$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.